2019
DOI: 10.1186/s13058-018-1088-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes promote breast cancer resistance to chemotherapy, a process amplified by obesity: role of the major vault protein (MVP)

Abstract: IntroductionClinical studies suggest that obesity, in addition to promoting breast cancer aggressiveness, is associated with a decrease in chemotherapy efficacy, although the mechanisms involved remain elusive. As chemotherapy is one of the main treatments for aggressive or metastatic breast cancer, we investigated whether adipocytes can mediate resistance to doxorubicin (DOX), one of the main drugs used to treat breast cancer, and the mechanisms associated.MethodsWe used a coculture system to grow breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 46 publications
2
78
1
Order By: Relevance
“…Third, these genes could have a true BMIincreasing effect. Consistent with our in silico finding, MVP is upregulated in adipocytes and cells co-cultured with adipocytes from obese individuals [86,87]. If KCTD13 and MVP have a true BMI-increasing effect, the 16p11.2 region contains both BMI-increasing and BMIdecreasing genes, and the effect of the BMI-decreasing genes is stronger.…”
Section: Ino80esupporting
confidence: 89%
“…Third, these genes could have a true BMIincreasing effect. Consistent with our in silico finding, MVP is upregulated in adipocytes and cells co-cultured with adipocytes from obese individuals [86,87]. If KCTD13 and MVP have a true BMI-increasing effect, the 16p11.2 region contains both BMI-increasing and BMIdecreasing genes, and the effect of the BMI-decreasing genes is stronger.…”
Section: Ino80esupporting
confidence: 89%
“…In addition, poor treatment outcomes are also reported in overweight and obese breast cancer patients evident by larger tumor sizes and poor clinical outcomes (7,18,42,43) especially those treated with doxorubicin (42,44). It was also reported that DIO decreased the efficacy of breast cancer treatment protocols in pre-clinical animal models (33,45).…”
Section: Diet-induced Obesity Significantly Decreased Doxorubicin Trementioning
confidence: 99%
“…Furthermore, a dysregulation of cytokines (i.e., increased IL-6, TNF-α, and IL-1β) and adipokines, such as increased leptin and decreased adiponectin (80)(81)(82)(83) has been shown to induces transcriptional changes. For example leptin has been shown to inhibit lipogenesis by altering the expression of transcription factors involved in lipid metabolism (7,45). The outcome is altered adipocyte endocrine functionality which can favor tumor cells to produce more adipokines (83).…”
Section: Diet-induced Obesity Distinctly Alters Lipid Metabolism In Tmentioning
confidence: 99%
“…Several studies reported that overweight and obesity elevate the risk of breast cancer, particularly in pre-and post-menopausal females [14] [15]. Clinical studies propose that obesity, besides promoting breast cancer aggressiveness, is associated with a decline in chemotherapy effectiveness, though the process intricate still indefinable [16].…”
Section: Discussionmentioning
confidence: 99%